2015
DOI: 10.1016/j.fluid.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Coarse grained force field for the molecular simulation of natural gases and condensates

Abstract: A c c e p t e d M a n u s c r i p t Highlights -A framework to obtain accurate coarse-grained force fields is described -Force field parameters are presented for compounds of interest -A methodology to simulate bubble points of complex mixtures is proposed. -The force fields are shown to be robust and transferrable Highlights (for review) AbstractThe atomistically-detailed molecular modelling of petroleum fluids is challenging, amongst other aspects, due to the very diverse multicomponent and asymmetric nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 79 publications
(70 reference statements)
6
107
0
2
Order By: Relevance
“…The model is obtained from a corresponding states parametrization of the SAFT equation of state [23], which provides force field parameters given the knowledge of the critical temperature, the acentric factor and a given liquid density. The parameters for this particular molecule have been described by Herdes et al [24] as λ = 18.41 ; ε/k B = 378.56 K and σ = 4.351 Å. In the case of the chain fluid, there is a restriction added by an angle bending potential between three consecutive beads, ψ = k(θ -θ 0 ) 2 where θ is the angle subtended by three consecutively bonded spheres.…”
Section: Pure Componentsmentioning
confidence: 99%
“…The model is obtained from a corresponding states parametrization of the SAFT equation of state [23], which provides force field parameters given the knowledge of the critical temperature, the acentric factor and a given liquid density. The parameters for this particular molecule have been described by Herdes et al [24] as λ = 18.41 ; ε/k B = 378.56 K and σ = 4.351 Å. In the case of the chain fluid, there is a restriction added by an angle bending potential between three consecutive beads, ψ = k(θ -θ 0 ) 2 where θ is the angle subtended by three consecutively bonded spheres.…”
Section: Pure Componentsmentioning
confidence: 99%
“…However, possibly, the most interesting feature of these equations is the direct and quantitative link to the underlying potential, such that information gathered experiments can be incorporated into intermolecular potentials of interest here, is to garner experience from the molecular simulation of vapor-liquid interfaces to directly feed into this framework, in order to build a robust and transferable model capable of predicting the properties of an interfacial system from a minimal amount of commonly available experimental information, such as critical constants (see Refs. [65][66][67][81][82][83][84][85][86][87] for a complete discussion).…”
Section: -21mentioning
confidence: 99%
“…Finally, following the general methodology proposed by Segura et al, 43,44 the molecular parameters of pure fluids can be calculated by forcing the EoS to exactly reproduce the experimental vapor pressure, the local slope of the vapor pressure curve, and the density and compressibility of the liquid phase at one single reference temperature in terms of the theory of displacements. 45,46 In this work we modeled THF as a single-and double-segment pearl-necklace model, without any additional electrostatic interactions, estimated from the corresponding states principle (or critical data) proposed by Mejía et al 41 This methodology has shown great flexibility to characterize vapor-liquid interfacial properties of pure fluids 47 and complex mixtures of dilute surfactant solutions 48 and natural gases and condensates. 47,[49][50][51] Table I summarizes the SAFT parameters for THF as used in molecular simulations in this work.…”
Section: A Saft-coarse Grained Mie Force Fieldmentioning
confidence: 99%
“…45,46 In this work we modeled THF as a single-and double-segment pearl-necklace model, without any additional electrostatic interactions, estimated from the corresponding states principle (or critical data) proposed by Mejía et al 41 This methodology has shown great flexibility to characterize vapor-liquid interfacial properties of pure fluids 47 and complex mixtures of dilute surfactant solutions 48 and natural gases and condensates. 47,[49][50][51] Table I summarizes the SAFT parameters for THF as used in molecular simulations in this work. Nevertheless, the methodology proposed by Mejía et al 41 cannot be used directly in a rigid configuration, because energy contribution in Eq.…”
Section: A Saft-coarse Grained Mie Force Fieldmentioning
confidence: 99%